2010
DOI: 10.1007/978-3-540-78716-7
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Aspects of Pediatric Fractures

Abstract: The use of general descriptive names, registered names, trademarks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use.Product liability: The publishers cannot guarantee the accuracy of any information about dosage and application contained in this book. In every individual case the user must check such information by consulting the relevant literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…Apart from the macroscopic and radiological scrutiny, few paleopathological studies have applied histological techniques to characterize different types of injury lesions [38,39,40,41,42,43,44,45] or to understand the timings of posttraumatic healing [46,47,48,49]. The results of this exploratory investigation showed that gross inspection may be insufficient to describe and characterize trauma lesions or to understand the biology of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the macroscopic and radiological scrutiny, few paleopathological studies have applied histological techniques to characterize different types of injury lesions [38,39,40,41,42,43,44,45] or to understand the timings of posttraumatic healing [46,47,48,49]. The results of this exploratory investigation showed that gross inspection may be insufficient to describe and characterize trauma lesions or to understand the biology of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal injuries may result in otherwise clinically normal infants because of a traumatic delivery such as a breech birth (Bilo et al, ). The most prevalent fracture related to birth trauma are clavicular fractures with an incidence of 0.2–4.4% of neonates (Collins and Reed, ).…”
Section: Skeletal Recognition Of Physical Abusementioning
confidence: 99%
“…The incidence of femoral fractures owing to birth trauma is 0.13 in 1,000 live births (Morris et al, 2002). The most common type of fracture was a spiral fracture of the proximal femur associated with twin births, birth with forceps, breech birth, premature births, and Cesarean delivery (Bilo et al, 2010). However, Collins and Reed (2014) Adapted from Kleinman (1998) and Abel (2011). reported that midshaft femoral fractures are most common in perinates.…”
Section: Birth Traumamentioning
confidence: 99%
“…Therefore histology is useful to differentiate between bone lesions that were sustained prior to death and lesions that are the effect of post-mortem damage. Also, experimental and clinical studies have shown that the bone tissue response after fracture or amputation follows a time-dependent sequence (Bilo et al, 2010). Therefore specific healing features can be used to determine the minimum amount of time elapsed between the trauma and eventual death (i.e., the "posttraumatic survival time").…”
Section: Mechanical Traumamentioning
confidence: 99%